Anterior–Posterior Patterning in Lepidopteran Wings - McKenna, Kenneth Z.; Kudla, Anna M.; Nijhout, H. Frederik (Frontiers in Ecology and Evolution, 2020)
The color patterns on the wings of butterflies and moths are among the most complex manifestations of pattern formation in nature. The complexities of these patterns arise from the diversification of a conserved set of homologous elements known as the Nymphalid Ground Plan that can change color, shift position, expand, or disappear altogether. Recent work has shown that the anterior-posterior axis of the butterfly wing may also have an important role in the development and evolution of wing-pattern diversity. Here we characterize the anterior-posterior axis by mapping expression domains of key regulatory genes onto the wing. We show that the butterfly wing can be subdivided into four primary regions, with the boundaries of these domains arising at the positions of the M1, M3, and Cu2 wing-veins. We find that the correlation among variation in the border ocelli is strongest for those within the same domain. We show how these domains may be used to determine phenotypic outcomes by surveying the frequency of color boundaries, tail development, and wing shape discontinuities across five major butterfly families: Lycaenidae, Nymphalidae, Papilionidae, Pieridae, and Riodinidae. Of the more than 200 genera we surveyed in this study, color pattern discontinuities emerge most often at the boundary veins M1, M3, and Cu2, and shape discontinuities and tails at veins M3 and Cu2. These findings reveal a hitherto unrecognized mode of evolution of patterning in the Lepidoptera.